Divinyl benzene-acryloyl chloride random copolymer, modified aluminum nitride, heat-conducting composite material and preparation method

By modifying the random copolymer of divinylbenzene-acryloyl chloride of aluminum nitride, the problems of poor compatibility with polymethylhydrogen siloxane and insufficient hydrolysis resistance of aluminum nitride are solved, and high thermal conductivity and good hydrolysis resistance of thermal composite materials are achieved.

CN119661767AInactive Publication Date: 2025-03-21NORTHWESTERN POLYTECHNICAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411958627.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-03-21
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The poor compatibility of aluminum nitride and polymethylhydrosiloxane limits the improvement of thermal conductivity, and aluminum nitride is easy to hydrolyze in humid air, reducing the thermal conductivity.

Method used

The aluminum nitride is modified by using divinylbenzene-acryloyl chloride random copolymer to improve its compatibility with polymethylhydrosiloxane and enhance its hydrolysis resistance, thereby improving the thermal conductivity of the thermal composite material.

Benefits of technology

The thermal conductivity of modified aluminum nitride and polymethylhydrogen siloxane composite materials has been significantly improved, the water absorption rate is reduced, the hydrolysis resistance is enhanced, and the interface thermal resistance is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119661767A_ABST
    Figure CN119661767A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of heat-conducting materials, and particularly relates to a divinyl benzene-acryloyl chloride random copolymer, modified aluminum nitride, a heat-conducting composite material and a preparation method of the divinyl benzene-acryloyl chloride random copolymer. According to the invention, tert-butyl acrylate is taken as a monomer, divinyl benzene is taken as a branching unit, and the divinyl benzene-acryloyl chloride random copolymer with a branching structure is synthesized through atom transfer radical polymerization. The divinyl benzene-acryloyl chloride random copolymer is grafted on the surface of the aluminum nitride, so that the hydrolysis resistance of the modified aluminum nitride and the interfacial compatibility of the modified aluminum nitride and polymethylhydrosiloxane are improved; the heat-conducting composite material prepared by taking the modified aluminum nitride as the heat-conducting filler has good heat-conducting property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of thermal conductive materials, and in particular relates to a divinylbenzene-acryloyl chloride random copolymer, modified aluminum nitride and a thermal conductive composite material and a preparation method thereof. Background Art

[0002] As electronic products are rapidly developing towards high power and integration, the problems of heat accumulation and heat dissipation are becoming more and more prominent, and higher requirements are placed on the thermal conductivity, insulation and heat resistance of thermal interface materials. Compared with traditional thermal interface materials (such as epoxy resin, polyurethane, etc.), polymethylhydrogensiloxane (PMHS) has the advantages of excellent insulation performance, aging resistance, easy molding and good compatibility with silicon substrates. It is an ideal matrix for preparing thermal interface materials, but it is usually necessary to fill a large amount of thermal conductive fillers into PMHS to obtain high thermal conductivity. Aluminum nitride (AlN), as a material with high thermal conductivity and excellent electrical insulation, is an ideal filler for preparing high thermal conductivity PMHS composites. However, AlN has poor compatibility with PMHS, which is not conducive to heat transfer and limits the improvement of the thermal conductivity of AlN / PMHS composites. In addition, AlN is easily hydrolyzed in humid air, reducing its thermal conductivity coefficient λ, thereby affecting the thermal conductivity. Summary of the invention

[0003] In view of this, the present invention provides a divinylbenzene-acryloyl chloride random copolymer, a modified aluminum nitride and a thermal conductive composite material and a preparation method. The divinylbenzene-acryloyl chloride random copolymer provided by the present invention is used to modify aluminum nitride, thereby improving the compatibility of the modified aluminum nitride with polymethylhydrogensiloxane and improving its hydrolysis resistance, thereby improving the thermal conductivity of the modified aluminum nitride and polymethylhydrogensiloxane composite thermal conductive material.

[0004] In order to solve the above technical problems, the present invention provides a divinylbenzene-acryloyl chloride random copolymer having a structure as shown in Formula 1:

[0005]

[0006] Among them, the sum of m and p is 5.5 to 18.0, and m and p cannot be 0;

[0007] The sum of n and q is 0.1 to 2.0, and n and q cannot be zero.

[0008] Preferably, the molecular weight of the divinylbenzene-acryloyl chloride random copolymer is 1000-20000 g / mol.

[0009] The present invention also provides a method for preparing the divinylbenzene-acryloyl chloride random copolymer described in the above technical solution, comprising the following steps:

[0010] tert-butyl acrylate, divinylbenzene, a ligand, an initiator, a catalyst and a first organic solvent are mixed to carry out copolymerization to obtain a divinylbenzene-tert-butyl acrylate random copolymer;

[0011] The divinylbenzene-tert-butyl acrylate random copolymer, an acyl chlorination agent and a second organic solvent are mixed to carry out an acyl chlorination reaction to obtain the divinylbenzene-acryloyl chloride random copolymer.

[0012] Preferably, the ligand comprises pentamethyldivinyltriamine or bipyridine, the initiator comprises methyl 2-bromopropionate, ethyl 2-bromoisobutyrate or toluene chloride, the catalyst comprises cuprous bromide or ferrous bromide, and the first organic solvent comprises N,N-dimethylacetamide;

[0013] The mass ratio of the tert-butyl acrylate to divinylbenzene is 1-10:1-9, the mass ratio of the tert-butyl acrylate to the ligand is 10-100:1-40, the mass ratio of the tert-butyl acrylate to the initiator is 1-10:2-20, the mass ratio of the tert-butyl acrylate to the catalyst is 10-100:1-50, and the mass ratio of the tert-butyl acrylate to the first organic solvent is 10-100:1-60;

[0014] The copolymerization reaction temperature is 25 to 150° C. and the reaction time is 1 to 24 hours.

[0015] Preferably, the chlorination agent includes one or more of thionyl chloride, oxalyl chloride and dichloromethane, and the second organic solvent includes one or more of tetrahydrofuran, dimethylformamide and dimethyl sulfoxide;

[0016] The mass ratio of the divinylbenzene-tert-butyl acrylate random copolymer to the chlorination agent is 1-60:1-60, and the mass ratio of the divinylbenzene-tert-butyl acrylate random copolymer to the second organic solvent is 1-60:1-50;

[0017] The acyl chlorination reaction time is 1 to 24 hours.

[0018] The present invention also provides a modified aluminum nitride, comprising aluminum nitride and a random copolymer grafted on the surface of the aluminum nitride;

[0019] The random copolymer is the divinylbenzene-acryloyl chloride random copolymer described in the above technical solution or the divinylbenzene-acryloyl chloride random copolymer prepared by the preparation method described in the above technical solution.

[0020] Preferably, the grafting amount of the random copolymer in the modified aluminum nitride is 0.1 to 5 wt%.

[0021] The present invention also provides a method for preparing the modified aluminum nitride described in the above technical solution, comprising the following steps:

[0022] The divinylbenzene-acryloyl chloride random copolymer, aluminum nitride and a third organic solvent are mixed and subjected to a reflux reaction to obtain the modified aluminum nitride.

[0023] Preferably, the third organic solvent includes one or more of tetrahydrofuran, dimethylformamide and dimethyl sulfoxide;

[0024] The mass ratio of the divinylbenzene-acryloyl chloride random copolymer to aluminum nitride is 1-50:10-800, and the mass ratio of the divinylbenzene-acryloyl chloride random copolymer to the third organic solvent is 1-50:10-600;

[0025] The temperature of the reflux reaction is 10-200° C., and the time is 1-8 hours.

[0026] The present invention also provides a thermally conductive composite material, comprising a matrix and a thermally conductive filler filled in the matrix;

[0027] The matrix is ​​polymethylhydrogensiloxane; the thermal conductive filler is the modified aluminum nitride described in the above technical solution or the modified aluminum nitride prepared by the preparation method described in the above technical solution.

[0028] Preferably, the mass percentage of the thermally conductive filler in the thermally conductive composite material is 5-90%.

[0029] The present invention also provides a method for preparing the thermally conductive composite material described in the above technical solution, comprising the following steps:

[0030] The polymethylhydrogensiloxane and the thermal conductive filler are mixed and then cured to obtain the thermal conductive composite material.

[0031] Preferably, the mass ratio of the polymethylhydrogensiloxane to the thermal conductive filler is 1-20:1-200;

[0032] The curing temperature is 25-200° C. and the curing time is 1-24 hours.

[0033] The present invention provides a divinylbenzene-acryloyl chloride random copolymer having a structure as shown in Formula 1: Wherein the sum of m and p is 5.5 to 18.0, and m and p cannot be 0; the sum of n and q is 0.1 to 2.0, and n and q cannot be 0. The modified aluminum nitride obtained by grafting the random copolymer provided by the present invention on the surface of aluminum nitride has good interfacial compatibility with polymethylhydrogensiloxane, and the defects and pores at the interface are relatively few, which is conducive to hindering the entry of water molecules. In addition, the branched structure of the random copolymer in the modified aluminum nitride can make the molecular chain network density at the interface of the thermally conductive composite material with modified aluminum nitride as a thermally conductive filler higher, and it is more difficult for water molecules to diffuse in, thereby giving it a relatively lower water absorption rate and relatively better hydrolysis resistance. The random copolymer provided by the present invention has a rich number of terminal functional groups and a strong chemical reaction activity, which can effectively improve the interfacial compatibility between the modified aluminum nitride and the polymethylhydrogensiloxane matrix. At the same time, the random polymer has the advantages of a small fluid dynamic radius and low viscosity, and has excellent processing performance. The thermally conductive composite material prepared by the blending and thermal curing process with modified aluminum nitride as a thermally conductive filler can be endowed with excellent thermal conductivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 The molecular weight distribution diagram of the divinylbenzene-acryloyl chloride random copolymer prepared in Examples 1 to 3;

[0035] Figure 2 FT-IR spectra of modified aluminum nitride prepared in Examples 4 to 6;

[0036] Figure 3 This is a TEM image of the modified aluminum nitride prepared in Example 4;

[0037] Figure 4 This is a TEM image of the modified aluminum nitride prepared in Example 5;

[0038] Figure 5 This is a TEM image of the modified aluminum nitride prepared in Example 6;

[0039] Figure 6 A columnar comparison chart of thermal conductivity of the thermally conductive composite materials prepared in Examples 7 to 12;

[0040] Figure 7 A columnar comparison chart of the interfacial thermal resistance of the thermally conductive composite materials prepared in Examples 7 to 12;

[0041] Figure 8 It is a dotted line graph of the water absorption rate of the thermally conductive composite materials prepared in Example 11 and Comparative Example 1;

[0042] Fig. 9 This is a columnar comparison chart of the thermal conductivity of the thermally conductive composite materials prepared in Example 11 and Comparative Example 1 before and after moisture-heat aging. DETAILED DESCRIPTION

[0043] The present invention provides a divinylbenzene-acryloyl chloride random copolymer having a structure as shown in Formula 1:

[0044]

[0045] Wherein, the sum of m and p is 5.5 to 18.0, can be 8.0 to 15.0, and can also be 10.0 to 13.0, and m and p cannot be 0;

[0046] The sum of n and q is 0.1 to 2.0, can be 0.5 to 1.5, and can also be 1.0 to 1.2. n and q cannot be zero.

[0047] As a specific embodiment of the present invention, the molecular weight of the divinylbenzene-acryloyl chloride random copolymer can be 1000-20000 g / mol, can be 2800-7900 g / mol, and can further be 5100 g / mol.

[0048] The present invention also provides a method for preparing the divinylbenzene-acryloyl chloride random copolymer described in the above technical solution, comprising the following steps:

[0049] tert-butyl acrylate, divinylbenzene, a ligand, an initiator, a catalyst and a first organic solvent are mixed to carry out copolymerization to obtain a divinylbenzene-tert-butyl acrylate random copolymer;

[0050] The divinylbenzene-tert-butyl acrylate random copolymer, an acyl chlorination agent and a second organic solvent are mixed to carry out an acyl chlorination reaction to obtain the divinylbenzene-acryloyl chloride random copolymer.

[0051] Unless otherwise specified in the present invention, all materials are conventional commercially available products.

[0052] The present invention mixes tert-butyl acrylate, divinylbenzene, a part, an initiator, a catalyst and a first organic solvent, and carries out copolymerization to obtain a divinylbenzene-tert-butyl acrylate random copolymer. As a specific embodiment of the present invention, the part can include pentamethyl divinyl triamine (PMDETA) or bipyridine, the initiator can include 2-bromopropionic acid methyl ester, 2-bromoisobutyric acid ethyl ester or toluene chloride, the catalyst can include cuprous bromide or ferrous bromide, and the first organic solvent can include N, N-dimethylacetamide (DMAc). The polymer monomer is a liquid phase organic matter, which can not dissolve the catalyst, and the catalyst cannot enter the reaction system, so it can not play a catalytic effect. In the present invention, the part can form a complex with the metal ion in the catalyst, so that the catalyst can be dissolved in the organic solvent, thereby realizing the catalytic effect of the catalyst.

[0053] As a specific embodiment of the present invention, the mass ratio of tert-butyl acrylate (tBA) to divinylbenzene (DVB) can be 1-10:1-9, or 2-6:1-9, or further 4-5:4-5, or specifically 4.5:4.3; the mass ratio of tert-butyl acrylate to ligand can be 10-100:1-40, or 20-60:5-20, or further 40-50:10-20, or specifically 45:14; the mass ratio of tert-butyl acrylate to initiator can be 1-10:2-20, It can also be 2-6:1-12, further can be 4-6:5-11, and can be specifically 4.5:10.2; the mass ratio of the tert-butyl acrylate to the catalyst can be 10-100:1-50, can also be 10-60:5-30, can further be 10-20:1-5, and can be specifically 10.2:1.8; the mass ratio of the tert-butyl acrylate to the first organic solvent can be 10-100:1-60, can also be 20-60:5-40, can further be 30-50:15-25, and can be specifically 45:20.

[0054] As a specific embodiment of the present invention, the mixing of tert-butyl acrylate, divinylbenzene, ligand, initiator, catalyst and the first organic solvent can be carried out under stirring. The present invention has no special requirements for the stirring, as long as the mixture can be mixed evenly.

[0055] As a specific embodiment of the present invention, the temperature of the copolymerization reaction can be 25 to 150°C, 30 to 100°C, and further 60 to 80°C; the time of the copolymerization reaction can be 1 to 24 hours, 1 to 20 hours, and further 5 to 10 hours. As a specific embodiment of the present invention, the copolymerization reaction can be carried out in a protective atmosphere, which can be argon or nitrogen.

[0056] As a specific embodiment of the present invention, the copolymerization reaction may further include:

[0057] The system after the copolymerization reaction is dropped into water to precipitate the copolymerization product and then filter to obtain a solid;

[0058] After the solid is dissolved, it is washed with water and dried in sequence to obtain the divinylbenzene-tert-butyl acrylate random copolymer.

[0059] As a specific embodiment of the present invention, the water used in the precipitation process may be deionized water; the present invention has no special limitation on the volume of water used in the precipitation process, and the conventional method in the art may be used. As a specific embodiment of the present invention, the filtration may be suction filtration. As a specific embodiment of the present invention, the dissolving solvent may be tetrahydrofuran. As a specific embodiment of the present invention, the water washing is to mix the dissolved solution and deionized water for sedimentation; the present invention may repeat the steps of dissolving and sedimentation 3 to 4 times until the washing solution is colorless and transparent. As a specific embodiment of the present invention, the drying may be vacuum drying, and the present invention has no special limitation on the vacuum drying, as long as the solvent can be removed.

[0060] After obtaining the divinylbenzene-tert-butyl acrylate random copolymer, the present invention mixes the divinylbenzene-tert-butyl acrylate random copolymer, an acyl chloride agent and a second organic solvent for acyl chloride reaction to obtain the divinylbenzene-acryloyl chloride random copolymer. As a specific embodiment of the present invention, the acyl chloride agent may include one or more of thionyl chloride, oxalyl chloride and dichloromethane, and may be specifically thionyl chloride; the second organic solvent may include one or more of tetrahydrofuran, dimethylformamide and dimethyl sulfoxide, and may be specifically tetrahydrofuran. As a specific embodiment of the present invention, the mass ratio of the divinylbenzene-tert-butyl acrylate random copolymer and the acyl chloride agent may be 1 to 60:1 to 60, or 5 to 40:5 to 40, or specifically 1:1; the mass ratio of the divinylbenzene-tert-butyl acrylate random copolymer and the second organic solvent may be 1 to 60:1 to 50, or 5 to 40:5 to 30, or specifically 2:1. As a specific embodiment of the present invention, the mixing of the divinylbenzene-tert-butyl acrylate random copolymer, the chlorination agent and the second organic solvent can be carried out under stirring. The present invention has no special limitation on the stirring, as long as the mixture can be uniformly mixed. As a specific embodiment of the present invention, the temperature of the chlorination reaction can be room temperature, the room temperature can be 20 to 35°C, and can also be 25 to 30°C; the time of the chlorination reaction can be 1 to 24 hours, and can also be 1 to 10 hours, and can further be 2 to 8 hours.

[0061] The present invention can regulate the molecular weight of the divinylbenzene-acryloyl chloride random copolymer by adjusting the ratio of the initiator to the tert-butyl acrylate monomer.

[0062] The invention uses tert-butyl acrylate as a monomer and divinylbenzene as a branching unit, and synthesizes a divinylbenzene-acryloyl chloride random copolymer with a branched structure through atom transfer radical polymerization (ATRP).

[0063] As a specific embodiment of the present invention, the acyl chlorination reaction may further include:

[0064] The system after the acyl chlorination reaction is subjected to rotary evaporation to obtain a solid;

[0065] The solid is dissolved in a second organic solvent and then distilled under reduced pressure, and the steps of dissolving and distilling under reduced pressure are repeated to obtain the divinylbenzene-acryloyl chloride random copolymer.

[0066] The present invention has no special requirements for the rotary evaporation, and the conventional method in the art can be used. The present invention can remove the second organic solvent in the system after the acyl chloride reaction by rotary evaporation. The present invention has no special requirements for the dissolution, as long as it can be completely dissolved. As a specific embodiment of the present invention, the steps of repeating the dissolution and vacuum distillation can be repeated 2 to 4 times. The steps of repeating the dissolution and vacuum distillation can remove the unreacted acyl chloride reagent and the residual second organic solvent, and further purify the divinylbenzene-acryloyl chloride random copolymer.

[0067] The present invention also provides a modified aluminum nitride, comprising aluminum nitride and a random copolymer grafted on the surface of the aluminum nitride;

[0068] The random copolymer is the divinylbenzene-acryloyl chloride random copolymer described in the above technical solution or the divinylbenzene-acryloyl chloride random copolymer prepared by the preparation method described in the above technical solution.

[0069] As a specific embodiment of the present invention, the grafting amount of the random copolymer in the modified aluminum nitride can be 0.1 to 5 wt %, can be 0.4 to 1.2 wt %, and can further be 0.8 to 1 wt %.

[0070] In the present invention, the modified aluminum nitride has excellent hydrolysis resistance and interface compatibility.

[0071] The present invention also provides a method for preparing the modified aluminum nitride described in the above technical solution, comprising the following steps:

[0072] The divinylbenzene-acryloyl chloride random copolymer, aluminum nitride and a third organic solvent are mixed and subjected to a reflux reaction to obtain the modified aluminum nitride.

[0073] As a specific embodiment of the present invention, the third organic solvent may include one or more of tetrahydrofuran, dimethylformamide and dimethyl sulfoxide, and may be specifically tetrahydrofuran. As a specific embodiment of the present invention, the mass ratio of the divinylbenzene-acryloyl chloride random copolymer to aluminum nitride may be 1-50:10-800, or 1-25:50-600, or further 1-3:200-500, or specifically 1:250, 2:250 or 3:250; the mass ratio of the divinylbenzene-acryloyl chloride random copolymer to the third organic solvent may be 1-50:10-600, or 1-25:550-400, or further 1-3:150-250, or specifically 1:200, 2:200 or 3:200.

[0074] As a specific embodiment of the present invention, the divinylbenzene-acryloyl chloride random copolymer, aluminum nitride and the third organic solvent can be mixed under stirring. The present invention has no special limitation on the stirring as long as the mixture can be mixed uniformly.

[0075] As a specific embodiment of the present invention, the temperature of the reflux reaction can be 10-200°C, or 25-100°C, or 50-80°C; the time of the reflux reaction can be 1-8h, or 2-6h.

[0076] The present invention also provides a thermally conductive composite material, comprising a matrix and a thermally conductive filler filled in the matrix;

[0077] The matrix is ​​polymethylhydrogensiloxane; the thermal conductive filler is the modified aluminum nitride described in the above technical solution or the modified aluminum nitride prepared by the preparation method described in the above technical solution.

[0078] As a specific implementation of the present invention, the mass percentage of the thermally conductive filler in the thermally conductive composite material is 5 to 90%, or may be 65 to 75%.

[0079] The present invention also provides a method for preparing the thermally conductive composite material described in the above technical solution, comprising the following steps:

[0080] The polymethylhydrogensiloxane and the thermal conductive filler are mixed and then cured to obtain the thermal conductive composite material.

[0081] As a specific embodiment of the present invention, the mass ratio of the polymethyl hydrogen siloxane to the thermal conductive filler can be 1-20:1-200, or 5-15:5-150, or further 5-7:130-150, and can be specifically 7:13 or 5:15.

[0082] As a specific embodiment of the present invention, the mixing of polymethyl hydrogen siloxane and the thermal conductive filler can be carried out under stirring. The present invention has no special limitation on the stirring as long as the mixture can be mixed evenly.

[0083] As a specific embodiment of the present invention, the curing may further include: subjecting the system after the polymethylhydrogensiloxane and the thermal conductive filler are mixed to vacuum degassing. The present invention has no special requirements for the vacuum degassing treatment, and the conventional method in the art can be used.

[0084] As a specific embodiment of the present invention, the curing temperature can be 25-200°C, or 50-150°C, or further 100-120°C; the curing time can be 1-24h, or 1-15h, or further 2-6h.

[0085] In order to further illustrate the present invention, the technical solutions provided by the present invention are described in detail below in conjunction with embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0086] The embodiment of the present invention has no special requirements on the order of magnitude of the mass of the material dosage, as long as the preparation is carried out according to the dosage ratio. The material dosage in the embodiment of the present invention is added according to the mass fraction.

[0087] Preparation of divinylbenzene-acryloyl chloride random copolymer:

[0088] Example 1

[0089] In an argon atmosphere, 1020 parts of methyl 2-bromopropionate, 450 parts of tert-butyl acrylate (tBA), 180 parts of CuBr, 140 parts of pentamethyldivinyltriamine (PMDETA), 430 parts of divinylbenzene (DVB) and 200 parts of N,N-dimethylacetamide (DMAc) were added to a Schlenk bottle, stirred and mixed evenly, and copolymerized at 60°C for 5 hours; the system after the copolymerization reaction was dropped into deionized water to precipitate the polymer, which was separated by suction filtration; the solid obtained by suction filtration was dissolved in tetrahydrofuran and mixed with deionized water for sedimentation, and the dissolution and sedimentation steps were repeated 4 times; the solid obtained by sedimentation was vacuum dried to obtain a divinylbenzene-tert-butyl acrylate random copolymer, which was recorded as PDVB-co-PtBA;

[0090] 200 parts of PDVB-co-PtBA, 100 parts of tetrahydrofuran (THF) and 200 parts of thionyl chloride (SOCl 2) was stirred to mix evenly and sealed. After the chlorination reaction at room temperature (30°C) for 2 hours, THF was removed by rotary evaporation. The solid after rotary evaporation was dissolved in THF and then distilled under reduced pressure. The steps of dissolution and distillation under reduced pressure were repeated 3 times to obtain a random copolymer of divinylbenzene and acryloyl chloride with a molecular weight of 2800 g / mol, which was recorded as PDVB-co-PACl.

[0091] Example 2

[0092] A divinylbenzene-acryloyl chloride random copolymer was prepared according to the method of Example 1, except that the amount of methyl 2-bromopropionate was changed from 1020 parts to 560 parts, and the molecular weight of the prepared divinylbenzene-acryloyl chloride random copolymer was 5100 g / mol.

[0093] Example 3

[0094] A divinylbenzene-acryloyl chloride random copolymer was prepared according to the method of Example 1, except that the amount of methyl 2-bromopropionate was changed from 1020 parts to 360 parts, and the molecular weight of the prepared divinylbenzene-acryloyl chloride random copolymer was 7900 g / mol.

[0095] The divinylbenzene-acryloyl chloride random copolymer prepared in Examples 1 to 3 was characterized by size exclusion chromatography to obtain the molecular weight and molecular weight distribution diagram as shown in Figure 1 shown.

[0096] Preparation of modified aluminum nitride:

[0097] Example 4

[0098] One part of PDVB-co-PACl with a molecular weight of 5100 g / mol prepared in Example 2, 250 parts of aluminum nitride (AlN) and 200 parts of tetrahydrofuran (THF) were stirred and mixed evenly, refluxed at 50° C. for 2 h, and filtered, washed and vacuum dried to obtain modified aluminum nitride with a surface grafting amount of 0.4 wt%, recorded as AlN@0.4wt%PDVB-co-PACl.

[0099] Example 5

[0100] Modified aluminum nitride was prepared according to the method of Example 4, except that the amount of PDVB-co-PACl was changed from 1 part to 2 parts, and the amount of PDVB-co-PACl grafted on the surface of the prepared modified aluminum nitride was 0.8wt%, recorded as AlN@0.8wt%PDVB-co-PACl.

[0101] Example 6

[0102] Modified aluminum nitride was prepared according to the method of Example 4, except that the amount of PDVB-co-PACl was changed from 1 part to 3 parts, and the amount of PDVB-co-PACl grafted on the surface of the prepared modified aluminum nitride was 1.2wt%, recorded as AlN@1.2wt%PDVB-co-PACl.

[0103] The modified aluminum nitride prepared in Examples 4 to 6 was characterized by Fourier transform infrared spectrometer, and the infrared spectrum was as follows: Figure 2 As shown. Aluminum nitride and modified aluminum nitride are both at 670 cm -1 A strong characteristic absorption peak appeared at 1730 cm-1, which corresponds to the stretching vibration of the Al-N bond. -1 The characteristic absorption peak of carbonyl group appeared at 670cm -1 The characteristic absorption peak of the Al-N bond broadened and the hydroxyl peak disappeared, which was mainly attributed to the condensation reaction between the hydroxyl groups on the AlN surface and the acyl chloride groups in the main chain and side chains to form covalent bonds, allowing PDVB-co-PACl to be successfully grafted on the AlN surface.

[0104] The modified aluminum nitride prepared in Examples 4 to 6 was examined by transmission electron microscopy, and the TEM images were as follows: Figures 3 to 5 As shown, Figure 3 This is the TEM image of the modified aluminum nitride prepared in Example 4. Figure 4 This is the TEM image of the modified aluminum nitride prepared in Example 5. Figure 5 This is a TEM image of the modified aluminum nitride prepared in Example 6. Figures 3 to 5 It can be seen that the PDVB-co-PACl layer grafted on the surface of the modified aluminum nitride prepared in Example 4 is incomplete, and its thickness is about 14.8 nm. The PDVB-co-PACl layer grafted on the surface of the modified aluminum nitride prepared in Example 5 is complete and has a uniform thickness, and its thickness is about 30.1 nm. The PDVB-co-PACl layer grafted on the surface of the modified aluminum nitride prepared in Example 6 has an uneven thickness and agglomeration phenomenon, and its thickness is 47.0 to 65.9 nm.

[0105] Preparation of thermally conductive composite materials:

[0106] Example 7

[0107] 70 parts of polymethylhydrogensiloxane (PMHS) matrix and 130 parts of AlN@0.4wt% PDVB-co-PACl thermal conductive filler prepared in Example 4 were stirred and mixed evenly, and then poured into a polytetrafluoroethylene mold. After vacuum degassing, the mixture was cured at 120°C for 2h to obtain a thermally conductive composite material with a thermal conductive filler mass percentage of 65%, which was recorded as AlN@PDVB-co-PACl / PMHS.

[0108] Example 8

[0109] A thermally conductive composite material was prepared according to the method of Example 7, except that the AlN@0.4wt%PDVB-co-PACl thermally conductive filler prepared in Example 4 was replaced by the AlN@0.8wt%PDVB-co-PACl thermally conductive filler prepared in Example 5.

[0110] Example 9

[0111] A thermally conductive composite material was prepared according to the method of Example 7, except that the AlN@P0.4wt%DVB-co-PACl thermally conductive filler prepared in Example 4 was replaced by the AlN@1.2wt%PDVB-co-PACl thermally conductive filler prepared in Example 6.

[0112] Example 10

[0113] 50 parts of polymethylhydrogensiloxane (PMHS) matrix and 150 parts of AlN@0.4wt% PDVB-co-PACl thermal conductive filler prepared in Example 4 were stirred and mixed evenly, and then poured into a polytetrafluoroethylene mold. After vacuum degassing, the mixture was cured at 120°C for 2h to obtain a thermally conductive composite material with a thermal conductive filler mass percentage of 75%, which was recorded as AlN@PDVB-co-PACl / PMHS.

[0114] Embodiment 11

[0115] A thermally conductive composite material was prepared according to the method of Example 10, except that the AlN@0.4wt%PDVB-co-PACl thermally conductive filler prepared in Example 4 was replaced by the AlN@0.8wt%PDVB-co-PACl thermally conductive filler prepared in Example 5.

[0116] Example 12

[0117] A thermally conductive composite material was prepared according to the method of Example 10, except that the AlN@0.4wt%PDVB-co-PACl thermally conductive filler prepared in Example 4 was replaced by the AlN@1.2wt%PDVB-co-PACl thermally conductive filler prepared in Example 6.

[0118] Comparative Example 1

[0119] A thermally conductive composite material was prepared according to the method of Example 11, except that the AlN@0.8wt% PDVB-co-PACl thermally conductive filler prepared in Example 5 was replaced with aluminum nitride (AlN). The prepared thermally conductive composite material was recorded as AlN / PMHS.

[0120] According to ISO 22007-2:2015 standard (determination of thermal conductivity and thermal diffusivity of plastics), the thermal conductivity (λ) of the thermally conductive materials prepared in Examples 7 to 12 and Comparative Example 1 was tested using a TPS2200 thermal constant analyzer of Hot-Disk Ltd. of Sweden, and the interfacial thermal resistance (ITR, for detailed calculation formulas, see Formulas 1 to 3) was calculated according to the Hamilton-Hasselman model. The results are listed in Table 1.

[0121]

[0122] Where: c is the thermal conductivity of the composite material; m is the thermal conductivity of the matrix; f is the thermal conductivity of the thermal conductive filler; V f is the volume fraction of thermal conductive filler; α is the phonon transmission probability; a is the average particle size of thermal conductive filler; Ψ is the sphericity of particles, usually taken as 0.7, and n is the empirical shape factor, taken as 4.3.

[0123] Table 1 Thermal conductivity of thermally conductive materials prepared in Examples 7 to 12 and Comparative Example 1

[0124]

[0125] Combined with Table 1, a columnar comparison chart of the thermal conductivity of the thermally conductive composite materials prepared in Examples 7 to 12 is drawn, as shown in FIG. Figure 6 Combined with Table 1, a columnar comparison chart of the interfacial thermal resistance of the thermally conductive composite materials prepared in Examples 7 to 12 is drawn, as shown in FIG. Figure 7 shown.

[0126] Combining Table 1 and Figure 6 , 7 It can be seen that the thermally conductive composite materials prepared in Examples 7 to 12 have higher thermal conductivity and lower interface thermal resistance than the thermally conductive material prepared in Comparative Example 1, indicating that the modified aluminum nitride provided by the present invention as a thermally conductive filler can improve the thermal conductivity of the thermally conductive composite material. Among them, Example 11 uses the modified aluminum nitride prepared in Example 5 as a thermally conductive filler, and the thermally conductive composite material with a thermally conductive filler content of 75% has the highest thermal conductivity, the lowest interface thermal resistance, and the best thermal conductivity.

[0127] After the thermally conductive composite materials prepared in Example 11 and Comparative Example 1 were immersed at room temperature (25° C.) for 80 hours, the water absorption of the thermally conductive composite materials was detected, and the results are listed in Table 2. The thermally conductive composite materials prepared in Example 11 and Comparative Example 1 were immersed in deionized water at 90° C. for 80 hours to perform a moisture and heat aging test, and the thermal conductivity of the thermally conductive composite materials before and after the moisture and heat aging test was respectively detected, and the results are listed in Table 2.

[0128] Table 2 Hydrolysis resistance and moisture-heat resistance of thermal conductive materials prepared in Example 11 and Comparative Example 1

[0129]

[0130] According to the water absorption detection process, a dotted line graph of the water absorption of the thermal conductive materials prepared in Example 11 (AlN@PDVB-co-PACl / PMHS) and Comparative Example 1 (AlN / PMHS) is drawn, as shown in FIG. Figure 8 According to the results in Table 1, a columnar comparison chart of the thermal conductivity of the thermal conductive materials prepared in Example 11 and Comparative Example 1 before and after moisture-heat aging is drawn, as shown in FIG. Fig. 9 shown.

[0131] Combining Table 2 and Figure 8 It can be seen that compared with the unmodified AlN / PMHS thermal conductive composite material, the water absorption rate of the AlN@PDVB-co-PACl / PMHS composite material is lower, which proves that the random copolymer modified thermal conductive filler improves the hydrolysis resistance.

[0132] Combining Table 2 and Fig. 9 It can be seen that after the same time of heat and humidity aging test, the performance retention rate of the AlN@PDVB-co-PACl / PMHS thermal conductive composite material λ is 99.1%, which is significantly better than the AlN / PMHS thermal conductive composite material (93.7%). This shows that the molecular chain network density at the interface of the AlN@PDVB-co-PACl / PMHS composite material is higher, and the interface under heat and humidity conditions is more stable.

[0133] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A divinylbenzene-acryloyl chloride random copolymer, characterized in that: It has the structure shown in Formula 1: Among them, the sum of m and p is 5.5 to 18.0, and m and p cannot be 0; The sum of n and q is 0.1 to 2.0, and n and q cannot be zero.

2. The divinylbenzene-acryloyl chloride random copolymer according to claim 1, characterized in that: The molecular weight of the divinylbenzene-acryloyl chloride random copolymer is 1000-20000 g / mol.

3. The method for preparing the divinylbenzene-acryloyl chloride random copolymer according to claim 1 or 2, characterized in that: The following steps are involved: tert-butyl acrylate, divinylbenzene, a ligand, an initiator, a catalyst and a first organic solvent are mixed to carry out copolymerization to obtain a divinylbenzene-tert-butyl acrylate random copolymer; The divinylbenzene-tert-butyl acrylate random copolymer, an acyl chlorination agent and a second organic solvent are mixed to carry out an acyl chlorination reaction to obtain the divinylbenzene-acryloyl chloride random copolymer.

4. The method for preparing the divinylbenzene-acryloyl chloride random copolymer according to claim 3, characterized in that: The ligand includes pentamethyldivinyltriamine or bipyridine, the initiator includes methyl 2-bromopropionate, ethyl 2-bromoisobutyrate or toluene chloride, the catalyst includes cuprous bromide or ferrous bromide, and the first organic solvent includes N,N-dimethylacetamide; The mass ratio of the tert-butyl acrylate to divinylbenzene is 1-10:1-9, the mass ratio of the tert-butyl acrylate to the ligand is 10-100:1-40, the mass ratio of the tert-butyl acrylate to the initiator is 1-10:2-20, the mass ratio of the tert-butyl acrylate to the catalyst is 10-100:1-50, and the mass ratio of the tert-butyl acrylate to the first organic solvent is 10-100:1-60; The copolymerization reaction temperature is 25 to 150° C. and the reaction time is 1 to 24 hours.

5. The method for preparing the divinylbenzene-acryloyl chloride random copolymer according to claim 3, characterized in that: The acyl chloride reagent includes one or more of thionyl chloride, oxalyl chloride and dichloromethane, and the second organic solvent includes one or more of tetrahydrofuran, dimethylformamide and dimethyl sulfoxide; The mass ratio of the divinylbenzene-tert-butyl acrylate random copolymer to the chlorination agent is 1-60:1-60, and the mass ratio of the divinylbenzene-tert-butyl acrylate random copolymer to the second organic solvent is 1-60:1-50; The acyl chlorination reaction time is 1 to 24 hours.

6. A modified aluminum nitride, characterized in that: It includes aluminum nitride and a random copolymer grafted on the surface of the aluminum nitride; The random copolymer is the divinylbenzene-acryloyl chloride random copolymer according to claim 1 or 2 or the divinylbenzene-acryloyl chloride random copolymer prepared by the preparation method according to any one of claims 3 to 5.

7. The modified aluminum nitride according to claim 7, characterized in that: The grafting amount of the random copolymer in the modified aluminum nitride is 0.1 to 5 wt %.

8. The method for preparing modified aluminum nitride according to claim 6 or 7, characterized in that: The following steps are involved: The divinylbenzene-acryloyl chloride random copolymer, aluminum nitride and a third organic solvent are mixed and subjected to a reflux reaction to obtain the modified aluminum nitride.

9. The method for preparing modified aluminum nitride according to claim 8, characterized in that: The third organic solvent includes one or more of tetrahydrofuran, dimethylformamide and dimethyl sulfoxide; The mass ratio of the divinylbenzene-acryloyl chloride random copolymer to aluminum nitride is 1-50:10-800, and the mass ratio of the divinylbenzene-acryloyl chloride random copolymer to the third organic solvent is 1-50:10-600; The temperature of the reflux reaction is 10-200° C., and the time is 1-8 hours.

10. A thermally conductive composite material, characterized in that: It comprises a matrix and a thermally conductive filler filled in the matrix; The matrix is ​​polymethylhydrogensiloxane; the thermal conductive filler is the modified aluminum nitride described in claim 6 or 7 or the modified aluminum nitride prepared by the preparation method described in claim 8 or 9.

11. The thermally conductive composite material according to claim 10, characterized in that: The mass percentage of the heat-conducting filler in the heat-conducting composite material is 5-90%.

12. The method for preparing the thermally conductive composite material according to claim 10 or 11, characterized in that: The following steps are involved: The polymethylhydrogensiloxane and the thermal conductive filler are mixed and then cured to obtain the thermal conductive composite material.

13. The method for preparing the thermally conductive composite material according to claim 12, characterized in that: The mass ratio of the polymethyl hydrogen siloxane to the thermal conductive filler is 1-20:1-200; The curing temperature is 25-200° C. and the curing time is 1-24 hours.